Experimental studies on pore wetting and displacement of fluid by CO2 in porous media - Li, Xingxun (The University of Edinburgh, 2015)
The study of multiphase flow in porous media is highly relevant to many problems of great scientific importance, such as CO2 storage and enhanced oil recovery. Even though significant progress has been made in these areas, many challenges still remain. For instance, the leakage of stored CO2 may occur due to the capillary trapping failure of cap rock. Approximately 70% of oil cannot be easily recovered from underground, because the oil is held in tight porous rocks. Although CO2 storage and enhanced oil recovery are engineering processes at a geological scale, they are predominantly controlled by the transport and displacement of CO2 and reservoir fluids in aquifers and reservoirs, which are further controlled by wetting and fluid properties at pore scale. This work focuses on experimental investigations of pore-scale wetting and displacement of fluids and CO2 in porous core samples. Pore wetting, which has been measured based on contact angle, is a principal control on multiphase flow through porous media. However, contact angle measurement on other than flat surfaces still remains a challenge. In order to indicate the wetting in a small pore, a new pore contact angle measurement technique is developed in this study to directly measure the contact angles of fluids and CO2 in micron-sized pores. The equilibrium and dynamic contact angles of various liquids are directly measured in single glass capillaries, by studying the effects of surface tension, viscosity and chemical structure. The pore contact angles are compared with the contact angles on a planar substrate. The pore contact angle of a confined liquid in a glass capillary differs from the contact angle measured on a flat glass surface in an open space. Surface tension is not the only dominant factor affecting contact angle. The static contact angle in a glass pore also varies with liquid chemical structure. Viscosity and surface tension can significantly affect the dynamic pore contact angle. A new empirical correlation is developed based on our experimental data to describe dynamic pore wetting. The CO2-fluid contact angle in porous media is an important factor affecting the feasibility of long-term permanent CO2 storage. It determines CO2 flow and distribution in reservoirs or aquifers, and thus ultimately finally the storage capacity. CO2-fluid contact angles were measured in small water-wet pores and oil-wet pores, investigating the effect of CO2 phase (gas/liquid/supercritical). The CO2 phase significantly affects the CO2-fluid contact angle in an oil-wet pore. Supercritical CO2-fluid contact angles are larger than gas CO2-fluid contact angles, but are smaller than liquid CO2-fluid contact angles. However, this significant CO2 phase effect on contact angle was not observed in a water-wet pore. Another key issue considered in this study is two-phase flow displacement in porous media. This strongly relates to the important macroscopic parameters for multiphase flow transport in porous media, such as capillary pressure and relative permeability. Here CO2-water displacements are studied by conducting CO2 flooding experiments in a sandstone core sample, considering the effects of CO2 phase, pressure and CO2 injection rate. The capillary pressure-saturation curve, water production behaviour and relative permeability are investigated for gas CO2-water, liquid CO2-water and supercritical CO2-water displacements in porous media. The pressure-dependant drainage capillary pressures are obtained as a result of CO2-water interfacial tension. Various water production behaviours are obtained for gas CO2-water and liquid CO2-water displacements, mainly due to the effect of CO2 dissolution. The significant irregular capillary pressure-saturation curves and water production behaviors can be observed for the supercritical CO2-water displacements. The water and CO2 relative permeabilities for CO2-water displacements in a porous media are then predicted.
Keywords: displacement; pore wetting; CO2 storage; enhanced oil recovery